Using UAS to Monitor and Quantify the Geomorphic Effects of extreme storms in tectonically active coastal areas: Evidence from Greece - Kotsi, E.; Vassilakis, Emm.; Diakakis, Μ.; Mavroulis, S.; Konsolaki, A.; Filis, C.; Lozios, S.; Lekkas, E. (EGU General Assembly, 2025)
Extreme weather events, increasingly frequent in the Mediterranean due to climate change, pose significant risks by triggering hydrogeomorphic processes such as slope failures. These phenomena, particularly prevalent in tectonically active and steeply sloped coastal areas, present challenges for monitoring due to their spatial and temporal dynamics.Unmanned aerial systems (UAS) and advanced photogrammetric techniques, including structure-from-motion (SfM) and multi-view stereo (MVS), have emerged as transformative tools for capturing high-resolution terrain data. This study employs UAS-aided photogrammetry alongside change detection methods, such as digital elevation models of differences (DoD) and cloud-to-cloud distance (C2C), to analyze geomorphic changes induced by extreme storms in highly visited and geologically dynamic coastal areas in Greece.The findings reveal the utility of UAS in providing detailed morphometric measurements, delineating areas of erosion and deposition, and identifying high-risk zones. These capabilities facilitate a deeper understanding of geomorphic processes, enabling informed risk assessment and management strategies. The study underscores the potential of integrating UAS and photogrammetry for continuous monitoring in regions with high socioeconomic and environmental value. This approach not only supports sustainable development by minimizing disruptions but also enhances safety standards in vulnerable, high-exposure coastal areas. Through this methodological framework, the research contributes to addressing the pressing need for resilient hazard management in the context of evolving climatic conditions.